Recent development on the synthesis of thiourea derivatives and effect of substituents on the anticancer activity: a short review - Roslan, Norashikin; Muhamad Bunnori, Noraslinda; Abdul Halim, Khairul Bariyyah; Kassim, Karimah; Mohd Aluwi, Mohd Fadhlizil Fasihi; Ngah, Nurziana (Malaysian Analytical Sciences Society (ANALIS), 2022)
Thiourea is a carbon, hydrogen, sulphur, and nitrogen-based organic molecule. The thiourea group has been improved by replacing various substituents for its hydrogen atoms at the nitrogen terminal, resulting in a wide range of biological activities, especially on anticancer properties. Despite the fact that thiourea derivatives have remarkable anticancer potential, finding a novel anticancer agent that is both safe and selective remains a challenge. This paper summarizes recent research on thiourea compounds that can be used to treat malignant cell lines. Several synthesis methods and the effects of substituents as well as their anticancer therapeutic potential in a variety of healthy and malignant cell lines are discussed. As a result, it is envisaged that this review will guide the design and synthesis of new thiourea derivatives in the future for the development of highly effective and selective anticancer drug